(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT The purpose of the study was to determine the work discipline of the village apparatus after the division in Buriko Village, Pitumpanua District, Wajo Regency. The number of informants in this study were 5 people. This type of research is qualitative with the type of qualitative research that emphasizes the subjectivity of human life experience. Data collection techniques using the method of observation, interviews and documentation. The results showed that the work discipline of the village apparatus after the division in Buriko Village, Pitumpanua District, Wajo Regency was not yet fully effective, this can be seen from the indicators (1) Preventive Discipline, Discipline attendance during the Pandemic period decreased so that people were still minimal to take care of all files related to the Office The village as well as uniform discipline and the presence of employees have not been thoroughly disciplined, because there are still staff who are seen hanging around outside the office during working hours. (2) Corrective Discipline, To improve discipline so that things do not happen that have been experienced by some people, the Village Head needs to improve further to supervise his staff who violates the identity of wearing casual clothes to the Village Office despite the pandemic, which can make people confused when they are in the village. Keywords: Discipline, Work, and Village Apparatus